5A's and 3A's Adolescent Smoking Interventions as Nicotine Dependence Endgame Initiatives in Sarawak, Malaysia - Muhammad Siddiq, Daud; Md Mizanur, Rahman; Sabrina, Lukas; Kamarudin, Kana; Merikan, Aren; Rudy Ngau, Ajeng; Mohd Faiz, Gahamat (Horizon Research Publishing Corporation, 2023)
Anti-smoking initiatives in Malaysia have the potential to reduce adolescent smoking, but their effectiveness and the need for research support remain important considerations. This study aimed to examine the efficacy of two smoking cessation interventions, the 5A's and 3A's, in reducing smoking among male adolescents in Samarahan, Sarawak. From September 2020 to June 2021, twelve communities were randomly assigned to the 5A's, 3A's, or control groups. A total of 519 participants aged 13-17 years provided data on demographics, smoking habits, nicotine dependency, motivation, carbon monoxide levels, and monthly cigarette consumption. The interventions' effectiveness was evaluated at 1, 3, 6 and 9 months. Analysis of covariance revealed no significant main effects of time or group on nicotine dependence, although age had a significant effect. Post hoc analyses showed significant group differences at multiple time points. For motivation, there was a significant main effect of time, with Group 5A consistently demonstrating higher means. Significant group differences were observed at specific time points. Analysis of carbon monoxide levels indicated significant main effects for group and time, with Group 5A consistently exhibiting the lowest mean levels. Significant group differences emerged by the 6th month. Regarding the number of cigarettes smoked, significant group differences were found, with both Group 5A and Group 3A reporting lower levels compared to the control group. Our findings add to the existing body of knowledge on the success of initiatives aimed at reducing smoking rates among young people. However, there is still a need for additional investigations in this field to further advance our understanding.